Clinical Efficacy of Two Different Methods to Initiate Sensor-Augmented Insulin Pumps: A Randomized Controlled Trial - Jesus Moreno-Fernandez; Francisco Javier Gómez; Maria Ángeles Gálvez Moreno; Justo P. Castaño (Journal of Diabetes Research)
Aim. To analyze clinical effect of a novel approach to initiate sensor-augmented insulin pumps in type 1 diabetes mellitus (T1DM) patients through early real-time continuous glucose monitoring (RT-CGM) initiation. Methods. A 26-week pilot study with T1DM subjects randomized (1 : 1) to start RT-CGM three weeks before continuous subcutaneous insulin infusion (CGM pre-CSII) or adding RT-CGM three weeks after continuous subcutaneous insulin infusion (CGM post-CSII). Results. Twenty-two patients were enrolled with a mean age of 36.6 yr. (range 19–59 yr.) and T1DM duration of 16.8±10.6 yr. Higher adherence in CGM pre-CSII patients was confirmed at study end (84.6±11.1% versus 64.0±25.4%; P=0.01). The two intervention groups had similar HbA1c reduction at study end of −0.6% (P=0.9). Hypoglycemic event frequency reduction was observed from baseline to study end only in CGM pre-CSII group (mean difference in change, −6.3%; 95% confidence interval, −12.0 to −0.5; P=0.04). Moreover, no severe hypoglycemia was detected among CGM pre-CSII subjects during the study follow-up (0.0±0.0 events versus 0.63±1.0 events; P=0.03). CGM pre-CSII patients showed better satisfaction than CGM post-CSII patients at the end of the study (27.3±9.3 versus 32.9±7.2; P=0.04). Conclusions. CGM pre-CSII is a novel approach to improve glycemic control and satisfaction in type 1 diabetes sensor-augmented pump treated patients.